2023
DOI: 10.3390/separations10010059
|View full text |Cite
|
Sign up to set email alerts
|

Moroccan Endemic Artemisia herba-alba Essential Oil: GC-MS Analysis and Antibacterial and Antifungal Investigation

Abstract: In Morocco, the endemic Artemisia herba-alba is well known by its traditional uses and health benefits. The search for natural, safe, and effective antibacterial and antifungal agents from plants is in high demand due to microbial and fungal resistance to conventional synthetic antibiotics and antifungal drugs. In this study, the A. herba-alba was collected from the region of Fez-Boulemane during the periods of March, June, and September. Essential oils (EOs) were extracted from the aerial part of the plant by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 70 publications
1
6
1
Order By: Relevance
“…The chemical composition of the essential oil ( Table 1 ) reveals a rich tapestry of volatile compounds, with α-thujone, β-thujone, and santolina alcohol as the predominant constituents. These findings align with those of Ouguirti et al [ 19 ] and Houti et al [ 20 ], who reported similar profiles in their studies of Artemisia species, emphasizing the consistency in essential oil composition across different geographical locations.…”
Section: Discussionsupporting
confidence: 91%
“…The chemical composition of the essential oil ( Table 1 ) reveals a rich tapestry of volatile compounds, with α-thujone, β-thujone, and santolina alcohol as the predominant constituents. These findings align with those of Ouguirti et al [ 19 ] and Houti et al [ 20 ], who reported similar profiles in their studies of Artemisia species, emphasizing the consistency in essential oil composition across different geographical locations.…”
Section: Discussionsupporting
confidence: 91%
“…Presently, a substantial quantity of information on the phytochemical properties has been accumulated for the plant extracts, resulting from the application of chromatography in conjunction with mass spectrometry detection and various methods of ionization [ 68 , 69 , 70 ]. The same applies to extracts and essential oils of various species of Artemisia L. The details of their phytochemical composition, derived from both qualitative and quantitative studies and given in [ 71 , 72 , 73 , 74 , 75 ], demonstrate the extensive array of bioactive compounds found in Artemisia L.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the value of these compounds, the plant's capacity for the biosynthesis of these kinds of compounds supported the plant's importance. Cubenol and its isomers were basically biosynthesized via the enzymatic reaction and rearrangement of germacrenyl cation inside the plant organs [46], while geranyl diphosphate, a pyrophosphate ester, was the starting and/or intermediate for the biosynthesis of many isoprenoids, including trans-chrysanthenyl acetate [47]. On the other side, farnesyl diphosphate was described as the main intermediate for the biosynthesis of terpenoids, including torreyol and sterols, in addition to carotenoidderived compounds [48].…”
Section: P Farcta Essential Oil Chemical Characterizationmentioning
confidence: 99%